The PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN DALAM PERSPEKTIF ISLAM (Studi pada Toko Emas H. M. Yasir (Aciak) Cabang Famili di Kota Siak Sri Indrapura) Gold Shop (Aciak) Famili Branch in Siak Sri Indrapura City) - Yessi Gassela (STAI Sulthan Syarif Hasyim, 2026)
This study aims to analyze the influence of price and product quality on consumer satisfaction from the perspective of Islamic economics at H. M. Yasir (Aciak) Gold Shop, Famili Branch in Siak Sri Indrapura City. This research used a quantitative approach with a survey method. The population of this study consisted of consumers who had purchased gold jewelry at the shop, totaling 1,197 consumers. The sampling technique used the Slovin formula to determine the number of respondents. Data were collected through questionnaires, interviews, and documentation. The data analysis techniques included validity tests, reliability tests, classical assumption tests, and hypothesis testing using multiple linear regression analysis. The results showed that price has an influence on consumer satisfaction because consumers tend to consider the suitability between the price and the benefits obtained from the product. In addition, product quality also has an influence on consumer satisfaction because good product quality can increase consumer trust and satisfaction. From the perspective of Islamic economics, fair pricing and good product quality reflect the principles of honesty and justice in business activities, which can create consumer satisfaction and trust. Keywords: Price, Product Quality, Consumer Satisfaction, Islamic Economics